A multi-interface software designed to share geometries within different simulation tools - Graça, João Mariz (2013)
A computer system that consists of a set of several programs that share both the same geometric definition and a consistent set of definitions for construction elements, is under development. The system consists of a common program allowing different types of exportation to other simulation programs or to other modules. The main modules under development until now are: an interface to the Energy Plus program, which builds an "idf" file from a 3D geometric definition that was previously modeled in graphical mode; and a module, that will provide the necessary calculations to verify if a given shape fulfills the thermal regulation of buildings which is based upon the Energy Performance of Buildings Directive (EPBD) approved by European Parliament and Council. An interface with Radiance program is also being developed. Using this system, which has been designed firstly for architectural conception, the user can perform different simulations with different aims, but sharing the same architectural shape and construction types, in order to check if the building fulfills thermal Portuguese codes and to perform energy simulations with Energy Plus or Radiance. The use of this system has demonstrated that it can represent a great saving of time in simulations and helping to reduce the occurrence of design errors as well. Since it allows performing simulations in a very quick way it can contribute also to help architects on achieving better solutions while designing, in terms of the optimization of all the parameter evaluated. The use of energy plus to evaluate the comfort of the buildings while being design as shown that this methodology can help to find more sustainable solutions in terms of their architectural shape and construction elements.